Optimizaition of a structure of machines’ fleet for winter maintainence of urban road network taking into account probabilistic assessment of climate factors - T. V. Bobrova; I. V. Sleptsov (Вестник СибАДИ)
The article dwells upon the model of optimization of the fleet of snowplows for winter maintain of the urban road network, taking into account the probability characteristics of the intensity of snowfall in a certain territory. As an optimal criterion there are taken minimal total costs in the transport sector and to eliminate negative effects of snowfalls on the road network of a city. The implementation of this approach is considered on the example of road maintainence service of Omsk.